Lepanthes arenasiana (Pleurothallidinae: Orchidaceae), a new species from Costa Rica - Bogarín, Diego (2010)
Lepanthes arenasiana from the Talamanca range in Costa Rica is described and illustrated. It is most similar to L. lancifolia but differs in having denticulate sepals, the petals with the upper lobe oblong, narrowing at apex and terminating as a short apicule, and the lower lobe basally ovate and straight, filiform towards the apex.